Optimal Retirement with Disability Pensions - Hans Fehr; Adrian Fröhlich (Center for Economic Studies and ifo Institute (CESifo), 2022)
This paper develops a general equilibrium life-cycle model with endogenous retirement and disability risk, in order to quantify the impact of recent pension reforms in Germany. At certain ages households may either apply for disability pensions (DP) or old-age pensions (OAP), de-pending on eligibility rules and the generosity of the two programs. Our policy analysis focus on the increase in the normal retirement age (NRA) from age 65 to 67 (Reform 2007) and the recent increase in the maximum assessment age (MAA) for DP benefits (Reform 2018). In contrast to the first reform, the second reform received hardly any attention in the public pension debate in Germany. Our simulation results indicate that with current eligibility and benefit rules, the second reform will almost neutralize the financial and economic benefits of the first reform. Consequently, securing the financial stability of the system will require a tightening of eligibility rules and/or a reduction of early retirement benefits in the future.
Keywords: C68; D91; H55; J24; 330; overlapping generations; stochastic general equilibrium; endogenous retirement; disability pensions